alpha-adrenergic antagonists as possible calcium channel inhibitors. - Atlas, D (1981)
The effects of various organic Ca2+ channel inhibitors were investigated on the binding of the alpha 1-antagonist 3H-labeled 2-[(2',6'-dimethoxyphenoxyethyl)aminomethyl]-1,4-benzodioxane ([3H]WB-4101) to membranes from rat brain and neuroblastoma-glioma hybrid cells (NG108-15). As found by monitoring binding of [3H]WB-41-1, the Ca2+ channel inhibitors methoxyverapamil (D600), verapamil, and the nifedipine analogue YC-93 bind to two different sites in rat brain: a high-affinity site (dissociation constant Kd = 2.9 nM and binding capacity B = 360 fmol/mg of protein) and a low-affinity site (Kd = 260 nM and B = 2700 fmol/mg of protein). In NG108-15 cells, where no alpha 1 receptors were detected with [3H]WB-4101, the Ca2+ antagonists were found to bind to nonadrenergic sites in the membrane with a capacity B = 976 fmol/mg of protein. The binding of Ca2+ antagonists to [3H]WB-41-1 sites led to the investigation of WB-4101 as a Ca2+ inhibitor by electrophysiological techniques. WB-4101 depressed the amplitude and reduced the rate of rise of the CA2+ spike with an affinity slightly greater than that observed for D600. The concentration for 50% inhibition of the Ca2+ spike amplitude was 48 microM for WB-4101 and 80 microM for D600. The WB-4101-induced blockade of the Ca2+ spike was antagonized by high Ca2+ concentrations, indicating a common site for Ca2+ and the alpha-antagonist. D600 and WB-4101 also inhibited voltage-dependent Na+ and K+ conductances. The results suggest that Ca2+ channels can account for a fraction of the sites labeled with [3H]WB-4101 in membrane preparations from brain and NG108-15 cells.